Operational Risk Analysis of Sharia Bank During Covid-19 Pandemic - Muhammad Isa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study is to evaluate the risk management practices used by PT Bank Syariah Indonesia KCP Indrapura in the years 2022. With a case study approach, this study employs a qualitative methodology. Interviews were the primary data gathering method employed in this study. The research's analytical method is explanation or explanation. According to the study's findings, operational risk is classified into two categories: customer risk and bank risk. These risks include limitations on service offices, increased operating costs, and even decreased profitability. Operational risk is caused by two types of causes: internal bank factors and external customer factors. Bank Syariah Indonesia KCP Indrapura works to mitigate operational risks by eliminating those that occur frequently enough.